Conflict in translation of children folklore songs - Abd Rahim, Normaliza; Nik Muhammad Affendi, Nik Rafidah; Roslan, Nur Maisarah; Roslan, Nur Widad; Roslan, Siti Nur Aliaa (International Journal of Scientific and Technology, 2020)
TRANSLATION is a process where a person has to go through reading several times in order to have a good text. A person who is good in translation will know the target language very well. As such, that person will be able to understand the text very well and the process of comprehensibility, predictability and readability [1] will take place smoothly. A translator work is considered as tedious since the translator has to go through the process over and over again. At present, machine translation has played a major role in making the process easier and faster as compared to the traditional dictionary. Translation in a classroom will take place in a second language classroom. As such, the process of translation will be taught in the beginning of the class. The students who involve in the translation process will go through the same process as the person who is good in translation [2]. Subsequently, the students will have conflict in translation since they have not mastered the language.